Quantitative Data Analysis for Language Assessment Volume I: Fundamental Techniques: edited by Raquel Aryadoust, and Michelle Raquel, 2019, New York, Routledge, xvi + 272 pp., 155.00 (hardcover), ISBN 9781138733121. Issue 2 (2nd April 2020) - Li, Gaoxin
ABSTRACT: Quantitative data analysis is a mainstream component in language assessment. First, this book review provides a brief review of its application in language assessment research in each chapter, and gives a theory-driven example of the application of the fundamental technique. Then, a summary is made of the 12 chapters in three sections, pointing out the book's strengths and limitations. Finally, this book review concludes with some recommendations for relevant readers.